UPAYA MENINGKATKAN KECERDASAN EMOSIONAL PADA UKM - Rodhiah; Sha, Thio Lie (Transpublika Publisher, 2023)
This Community Service Program (PKM) aims to introduce the role of emotional intelligence in entrepreneurship. The PKM activity partner is a recycling business owner who processes used plastic bottles into handicraft products such as decorative lamps, aquariums, flower pots, and others. The partner business is located in South Tangerang. This activity is a continuation of the previous PKM and was inspired by the partner's problems in marketing recycled products that have been processed. Based on initial observations made directly with partners, the main problem faced lies in the lack of understanding of emotional intelligence. Due to limited knowledge of emotional intelligence, the efforts made by partners have not been able to achieve optimal success. The method proposed in this activity is training or socialization conducted online with support from students as facilitators. The results of the activity showed that the implementation went smoothly. There was productive communication and discussion between the PKM team and partners. The enthusiasm of the partners can be seen in their interest in the material presented during the training.